A Study on Liqid- Liquid Etraction on Iron(III) With 2,5- Diphenyi Oxazole - Hussain, A. F (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
A study on  liquid- liquid extraction  of Iron (III) in Benzene has  been made. The effect of different parameters such as type of medium and time of equilibration,  concentration  of metal  ion, type of organic  solvent,  and effect of cations on distribution ratio of Iron (III). Has been studies the stoichiometry   of  the  extracted  species  determined   using  slope  analysis method and found to be (M:L) (1 :3).